A Toxoplasma gondii Ortholog of Plasmodium GAMA Contributes to Parasite Attachment and Cell Invasion - My-Hang Huynh (American Society for Microbiology, 2016)
ABSTRACT Toxoplasma gondii and its Plasmodium kin share a well-conserved invasion process, including sequential secretion of adhesive molecules for host cell attachment and invasion. However, only a few orthologs have been shown to be important for efficient invasion by both genera. Bioinformatic screening to uncover potential new players in invasion identified a previously unrecognized T. gondii ortholog of Plasmodium glycosylphosphatidylinositol-anchored micronemal antigen (TgGAMA). We show that TgGAMA localizes to the micronemes and is processed into several proteolytic products within the parasite prior to secretion onto the parasite surface during invasion. TgGAMA from parasite lysate bound to several different host cell types in vitro, suggesting a role in parasite attachment. Consistent with this function, tetracycline-regulatable TgGAMA and TgGAMA knockout strains showed significant reductions in host cell invasion at the attachment step, with no defects in any of the other stages of the parasite lytic cycle. Together, the results of this work reveal a new conserved component of the adhesive repertoire of apicomplexan parasites. IMPORTANCE Toxoplasma gondii is a successful human pathogen in the same phylum as malaria-causing Plasmodium parasites. Invasion of a host cell is an essential process that begins with secretion of adhesive proteins onto the parasite surface for attachment and subsequent penetration of the host cell. Conserved invasion proteins likely play roles that were maintained through the divergence of these parasites. Here, we identify a new conserved invasion protein called glycosylphosphatidylinositol-anchored micronemal antigen (GAMA). Tachyzoites lacking TgGAMA were partially impaired in parasite attachment and invasion of host cells, yielding the first genetic evidence of a specific role in parasite entry into host cells. These findings widen our appreciation of the repertoire of conserved proteins that apicomplexan parasites employ for cell invasion.